Age-related neuroinflammatory changes negatively impact on neuronal function - Lynch, Marina A. (Frontiers in Aging Neuroscience, 2010)
Neuroinflammatory changes, characterized by an increase in microglial activation and often accompanied by upregulation of inflammatory cytokines like interleukin-1β (IL-1β), are common to many, if not all, neurodegenerative diseases. Similar, though less dramatic neuroinflammatory changes are also known to occur with age. Among the consequences of these changes is an impairment in synaptic function and the evidence suggests that inflammatory cytokines may be the primary contributory factor responsible for the deficits in synaptic plasticity which have been identified in aged rodents. Specifically a decrease in the ability of aged rats to sustain long-term potentiation (LTP) in perforant path-granule cells of the hippocampus is associated with increased microglial activation. This review considers the evidence which suggests a causal relationship between these changes and the factors which contribute to the age-related microglial activation, and reflects on data which demonstrate that agents which inhibit microglial activation also improve ability of rats to sustain LTP. <input id="gwProxy" type="hidden" /> <!--Session data--> <input id="jsProxy" onclick="jsCall();" type="hidden" />